2012
DOI: 10.1073/pnas.1121176109
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insight into the blocking of CO diffusion in [NiFe]-hydrogenase mutants through multiscale simulation

Abstract: [NiFe]-hydrogenases are fascinating biological catalysts with potential application in biofuel cells. However, a severe problem in practical application is the strong sensitivity of hydrogenase to gaseous inhibitor molecules such as CO and O 2 . Recently, a number of successful protein engineering studies have been reported that aimed at lowering the access of diatomic inhibitors to the active site pocket, but the molecular mechanism conferring increased resistance remained unclear. Here we use a multiscale si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
79
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 52 publications
(83 citation statements)
references
References 37 publications
0
79
4
Order By: Relevance
“…The rate k i of conversion from A to I in eq 1 can be calculated from the rate constants in the following scheme: 24,25 boldFboldeboldFbolde(A)k1k+1[normalO2]boldFboldeboldFboldeO2(G)k2k+2boldFboldeboldFboldeO2(I)Above, k +1 is the second-order rate constant for the diffusion of O 2 from the solvent to the active site and k − 1 is the first-order rate constant for the diffusion in the opposite direction. In the resulting state G (for “Geminate”), O 2 is in the active site pocket but it is not yet chemically bound to the active site.…”
Section: Resultsmentioning
confidence: 99%
“…The rate k i of conversion from A to I in eq 1 can be calculated from the rate constants in the following scheme: 24,25 boldFboldeboldFbolde(A)k1k+1[normalO2]boldFboldeboldFboldeO2(G)k2k+2boldFboldeboldFboldeO2(I)Above, k +1 is the second-order rate constant for the diffusion of O 2 from the solvent to the active site and k − 1 is the first-order rate constant for the diffusion in the opposite direction. In the resulting state G (for “Geminate”), O 2 is in the active site pocket but it is not yet chemically bound to the active site.…”
Section: Resultsmentioning
confidence: 99%
“…This is a kinetic two-step model consisting of an initial diffusion step of the gas molecule, followed by a metal-gas molecule chemical reaction step (Wang et al., 2011, Wang and Blumberger, 2012). Here, a classical force-field (FF) was employed, and only the diffusion and binding of O 2 gas molecules to the RNR iron center were modeled:RNR(Fe)+normalO2k1k+1RNR(Fe)normalO2.…”
Section: Methodsmentioning
confidence: 99%
“…The nuanced role of the protein matrix in influencing catalysis is not restricted to oxygen delivery. In hydrogenases, gas channels have been reported to selectively filter molecules such as oxygen and carbon monoxide to prevent inactivation at the active site (12,17,35). Recent investigation of heme nitric oxide/oxygen binding domains has suggested that tunnels not only direct gases to the heme iron but also modulate reversible gas binding (16).…”
Section: Discussionmentioning
confidence: 99%